2024
DOI: 10.3390/biomedicines12040924
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin in Participants with or without Insulin Resistance and Diabetes

Lei Zhao,
Jonathan Zhou,
Fahim Abbasi
et al.

Abstract: Chemerin is a chemokine/adipokine, regulating inflammation, adipogenesis and energy metabolism whose activity depends on successive proteolytic cleavages at its C-terminus. Chemerin levels and processing are correlated with insulin resistance. We hypothesized that chemerin processing would be higher in individuals with type 2 diabetes (T2D) and in those who are insulin resistant (IR). This hypothesis was tested by characterizing different chemerin forms by specific ELISA in the plasma of 18 participants with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The data in this study show that individuals with T2D who differ in terms of their BMI had different levels of chemerin processing (Figure 1); however, the HbA1c levels did not influence the levels of chemerin processing (Figure 2). In contrast, our companion study showed that the levels of plasma glucose correlated with both the levels of chemerin and the amount of its cleavage, but that BMI was a very significant confounding factor (Zhao et al, Biomedicines in press) [46]. Taking these two studies together suggests that the effects of both BMI and T2D on chemerin levels are not independent of each other but, instead, take place via a common mediator.…”
Section: Discussionmentioning
confidence: 70%
“…The data in this study show that individuals with T2D who differ in terms of their BMI had different levels of chemerin processing (Figure 1); however, the HbA1c levels did not influence the levels of chemerin processing (Figure 2). In contrast, our companion study showed that the levels of plasma glucose correlated with both the levels of chemerin and the amount of its cleavage, but that BMI was a very significant confounding factor (Zhao et al, Biomedicines in press) [46]. Taking these two studies together suggests that the effects of both BMI and T2D on chemerin levels are not independent of each other but, instead, take place via a common mediator.…”
Section: Discussionmentioning
confidence: 70%